Joule heating effect on radiating MHD mixed convection stagnation point flow along vertical stretching sheet embedded in a permeable medium and heat generation/absorption. Issue 8 (24th July 2022) - Mehta, Ruchika; Kumar, Ravindra; Rathore, Himanshu; Singh, Jagdev
Abstract: The goal of this study is to investigate magnetohydrodynamics varied convective stagnation point stream with a vertically extended sheet embedded in a permeable material. Warmth generation/absorption, radiation impacts, and viscous dissipation are all considered. Using the process of likeness change, the principal boundary layer equations are written and turned into nonlinear ordinary joined differential equations, and the numerical result is produced using the Runge–Kutta fourth‐order approach via shooting technique. Varied physical limits have different effects, such as velocity fraction restriction, mixed convection restriction, Hartmann numeral, Prandtl numeral, permeability restriction, warm air radiation restriction, hotness generation/absorption restriction, and so on, over velocity and temperature scatterings are introduced graphically and then mathematically. The skin friction constant, in addition to Nusselt numerals, over the sheet is determined, expressed mathematically as well as introduced through tables. Fluid velocity and temperature increase with radiation restriction Ra. Skin friction and Nusselt numeral are increasing functions of Hartmann numeral Ha, and decreasing ones of permeability restriction K .